Superior Community Empowerment and Family Management Technology in Overcoming FOMO in Cigalontang Tasikmalaya Village Residents - Ujang Eri Jaenudin; Dheri Febiyani lestari; Isyana Rahayu; Raisa Hillia Aini Syifa; Adi Muhammad Nur Ihsan; Sri Sudiarti; Herdiyanti; Heidi Siddiqa; Taupik Akbar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Within the scope of the village, FOMO (Fear of Missing Out) can appear as concerns about being left behind in social and economic development, such as not being able to keep up with new trends or not benefiting from government programs introduced in other areas. This community service aims to provide training regarding superior community empowerment in optimizing family management technology to overcome FOMO and integrate family education for the residents of Kampung Ngenol, Cigalontang Village, Tasikmalaya. The research method used is to provide counseling or training. The results of the service have succeeded in increasing community empowerment through optimizing family management technology which can help overcome FOMO and integrate family education in village communities.  This is demonstrated by increasing public understanding and awareness of the importance of family management, the use of appropriate technology, and the integration of family education in everyday life.